Pelatihan Pembuatan Story Book Berbasis AI (Artificial Intelegent) untuk Penguatan Karakter Religius di Sekolah Dasar - Ahmad Rosyid; Meidawati Suswandari; Nurratri Kurniasari; Moefty Mahendra; Singgih Subiyantoro (Universitas Negeri Semarang, 2026)
This community service program aimed to enhance teachers’ competence in developing innovative learning media through training in creating story books based on Artificial Intelligence (AI) as a means of strengthening the religious character of elementary school students. The methods applied included observation, socialization, counseling, mentoring, and evaluation using pre-tests and post-tests. The training was conducted at SD Negeri 3 Dlepih with nine participants, consisting of teachers and the school principal. The results indicated a significant improvement in participants’ understanding and skills. The average score increased from 19 in the pre-test to 34 in the post-test, reflecting a rise of approximately 74%. Moreover, participants successfully produced AI-based story books ready to be implemented in classroom learning. Thus, this training proved effective in enhancing teachers’ ability to utilize technology while simultaneously supporting the reinforcement of students’ religious character through creative, contextual, and engaging learning media.